2012
DOI: 10.1111/j.1365-2133.2011.10669.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA expression in mycosis fungoides

Abstract: Altered expression of studied microRNAs and the differences between early and advanced MF may suggest that microRNAs play a significant role in MF pathogenesis. It seems that microRNAs could serve as potential therapeutic targets in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
3
30
2
1
Order By: Relevance
“…Patients were of a variety of carcinomas, including breast cancer, pancreatic ductal adenocarcinomas, esophageal cancer, hepatocellular carcinoma, leukemia, colorectal cancer, lung cancer and lymphoma. Of all the 28 studies, 16 studies (n = 2536) with HR data could be included for metaanalysis [7,[13][14][15][16][17][18][33][34][35][36][37][38][39][40][41]. Among them, seven studies (n = 1678) recruited lung cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were of a variety of carcinomas, including breast cancer, pancreatic ductal adenocarcinomas, esophageal cancer, hepatocellular carcinoma, leukemia, colorectal cancer, lung cancer and lymphoma. Of all the 28 studies, 16 studies (n = 2536) with HR data could be included for metaanalysis [7,[13][14][15][16][17][18][33][34][35][36][37][38][39][40][41]. Among them, seven studies (n = 1678) recruited lung cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…They may have oncogenic or tumor suppressing properties depending on their target genes (6,7). Several studies have demonstrated specific miRNA expression profiles in different types of CTCL suggesting a role in the pathogenesis of these disorders (8)(9)(10)(11)(12). For instance, recently, van Kester et al (8) have elaborated on the miRNA expression profile of tumor-stage mycosis fungoides (MF), a CTCL with a 10-year DSS of 42%.…”
Section: Introductionmentioning
confidence: 99%
“…Ralfkiaer et al (14) found that miR-155 was one of the most significantly upregulated miRs in several types of cutaneous T-cell lymphoma (CTCL) including MF compared with inflammatory skin diseases. The comparison between early stage and advanced stage has been described recently by Maj et al (15). No significant difference was found in miR-155 expression between early and advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that miR-155 is an oncogenic miR that was found to be overexpressed in various solid tumors and in B-cell lymphoid malignancies (5)(6)(7)(8)(9)(10)(11). Studies of the role of miR-155 in T-cell lymphomas in general and MF in particular are strikingly sparse (12)(13)(14)(15). Van Kester et al (13) found miR-155 to be upregulated in tumor-stage MF compared with benign inflammatory dermatoses (13).…”
Section: Introductionmentioning
confidence: 99%